I, Michael Bennett - Patterson, James, 1947-; Ledwidge, Michael (New York : Little, Brown and Co. ; Grand Central Publishing, 2012)
Detective Michael Bennett takes his family to upstate New York in an effort to escape a lawless crime wave erupting in Manhattan, only to find himself immersed in another nightmare, one that endangers his relationship with his wife.
Publishers, dates or pagination may vary.
Keywords: Bennett, Michael -- (Fictitious character) -- Fiction; Police -- New York (State) -- New York -- Fiction; Organized crime -- Fiction; Hispanic American gangs -- Fiction; Police -- Violence against -- Fiction; Thrillers (Fiction)